Genotoxic Effect of Amoxicillin on Peripheral Blood of Common Carp (Cyprinus carpio) - Elizalde Velazquez, Armando; Bernadac, Gerardo; Martinez Rodriguez, Hector; Galar Martínez, Marcela; Dublan, Octavio; Gómez Oliván, Leobardo Manuel (Springer, Cham, 2019)
Amoxicillin (AMX), one of the most commonly prescribed antibiotics around the globe, has been found in diverse environmental water bodies, which have raised the concern of its possible toxicological effects on nontarget aquatic species. This study aimed to evaluate the potential genotoxic effects of AMX in peripheral blood of the common carp Cyprinus carpio using the comet assay. Teleost fish were exposed to different concentrations (10 ng/L, 10 μg/L, and 10 mg/L) for different exposure times (12, 24, 48, 72, and 96 h). Additionally, the AMX and its main degradation product, amoxicilloic acid (AMA), were determined by high-performance liquid chromatography techniques coupled to a UV and an electrochemical detector (HPLC-EC). Results show a statically significant time concentration-dependent increase in DNA damage at 24 and 48 hours. No amoxicillin was detected at any time and at any concentration in any system tested, but amoxicilloic acid was detected and even quantified in water and blood since the beginning of the experiment. Amoxicilloic acid has the capacity to increase the amount of reactive oxygen species via hypersensitivity reactions, which are the responsible of the DNA damage in the blood lymphocytes of Cyprinus carpio.